Analysing change in transnational policy networks: legitimacy-transfers in the Bologna Process - Alexander-Kenneth Nagel (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2007)
Drawing on theories of legitimacy and democratic deficits in international politics this paper provides an actor-centered relational approach of mapping legitimacy-flows within the transnational policy network of the Bologna Process for a European Higher Education Area. It is shown that legitimacy (either in the form of symbolical or institutional capital conveyed in political speech acts) can be treated as a matter of exchange and bargaining just as other resources, such as money or information. The legitimacy-network of the Bologna Process does not reflect the often lamented lack of democracy in international political setting. While transfers of legitimacy are the most prevalent type of relation in the policy network, there is no unidirectional flow from national societal actors to supranational public actors, but rather a polyvalent exchange. With respect to legitimacy as a political resource the Bologna Process is therefore not hierarchical, it is a bazaar.
Keywords: 370; EU-Bildungspolitik; Hochschulpolitik; Legitimität; EU-Staaten